2004
DOI: 10.5089/9781451875140.001
|View full text |Cite
|
Sign up to set email alerts
|

Social Spending, Human Capital, and Growth in Developing Countries: Implications for Achieving the Mdgs

Abstract: This Working Paper should not be reported as representing the views of the IMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 42 publications
8
71
2
8
Order By: Relevance
“…This is not surprising in a country with poor institutions that encourage rent seeking behaviour and poor enforcement of rule of law that discourage long term planning with respect to urban planning and provision of social infrastructures to match population growth rate and government efficiency, increase urban population will result into urbanization and its associated problems that worsen health situations. This is in contrast with the study of Anyawu et al (2007) and Baldacci et al (2004) that only confirmed a negative but insignificant relationship with health sectors performance.…”
Section: 2: Long Run Estimatescontrasting
confidence: 56%
See 1 more Smart Citation
“…This is not surprising in a country with poor institutions that encourage rent seeking behaviour and poor enforcement of rule of law that discourage long term planning with respect to urban planning and provision of social infrastructures to match population growth rate and government efficiency, increase urban population will result into urbanization and its associated problems that worsen health situations. This is in contrast with the study of Anyawu et al (2007) and Baldacci et al (2004) that only confirmed a negative but insignificant relationship with health sectors performance.…”
Section: 2: Long Run Estimatescontrasting
confidence: 56%
“…Higher values of CIM (1) indicate a greater reliance on or preference for long-term contracts and high degree of trust in the economy while a lower value of CIM (0) indicates absolute lack of trust in the economy. LIT: Literacy rate is an important determinant of the health status of infants and children, as well as the population in general (see Baldacci et al, 2004;World Bank, 1993;Schulz, 1993) proxy by total government expenditure on education. Literacy rate is positively associated with infants' health and consequently reduces infant mortality rate.…”
Section: 3: Variables Measurement Hspmentioning
confidence: 99%
“…Based on the results of a regression analysis carried out with panel data on 120 development countries, 2 the authors (Baldacci et al 2004) argue that not only are higher expenditures for education and governance reforms essential for reaching MDGs 2 and 8 respectively, greater efforts here are also by far the most effective and efficient approach when it comes to (i) accelerating economic growth; (ii) reducing income poverty and hunger (MDG 1), (iii) improving gender equality (MDG 3) and (iv) reducing child mortality rates (MDG 4) (See Overview 7).…”
Section: Neglect Of Multi-causalitiesmentioning
confidence: 99%
“…There are empirical studies that confirm human capital is important for long-run growth (see, e.g., Romer, 1986;Barro, 1991;Levine and Renelt, 1992;Mankiw et al, 1992;Barro and Lee, 1993;Bassanini and Scarpetta, 2001;Krueger and Lindahl, 2001;Baldacci et al, 2004). …”
Section: Introductionmentioning
confidence: 99%